Robust High Resolution Fat-Water Separation in the Abdomen during Free-Breathing by Self-Gated 2D Radial TrueFISP Imaging - Riad S. Ababneh; Thomas Benkert; Felix A. Breuer (Jordan Journal of Physics, 2025)
Accurate high resolution fat-water separation in the abdomen is challenging due to respiratory motion. In this work, we propose a robust high resolution fat-water separation strategy in the abdomen during free breathing by employing radial sampling with a golden angle increment. To this end, a radial TrueFISP sequence was modified enabling the echo time TE to change from projection to projection, to force fat signals to behave in a conspicuous manner through time, so that they can be detected and separated from water signals through temporal processing. Thus, the center signal (DC) of each radial readout can then be used for respiratory gating, allowing the generation of multiple images at different TEs at multiple breathing states. Finally, any fat-water separation technique can be used to synthesize high resolution fat and water images at arbitrary breathing states. Good separation of fat and water signals was achieved using the radial TrueFISP sequence during free breathing without streaking artifacts or blurring due to respiratory motion. Keywords: Fat-water separation; TrueFISP; Self-gating; Dynamic imaging; Free breathing.